Perbandingan Penggunaan Kontrasepsi Suntik Zat Tunggal dan Kombinasinya terhadap Kejadian Reaksi Obat yang Tidak Dikehendaki di Satu Bidan Praktek Kota Depok - Rahmawati, Ni Made Ayu; Andrajati, Retnosari; Supardi, Sudibyo (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Injectable contraceptives raise health problems risk than oral or implan contraceptive. This study aimed to compare the incidence of adverse drug reactions (ADRs) single injectable contraceptive use (Depot medroxyprogesterone acetat/DMPA) with a combination of injectable contraceptive (CICs) use (DMPA and Estradiol cypionate/E2C). The study design was a cross-sectional two population comparison. The sample consisted of 88 acceptors in each group. The ADRs were analyzed using Chi Square and logistic regression multivariate. The largest side effect in single injectable contraceptive group were menstrual disorders (86,4%) and mood dischange, while the side effects in CICs group were mood (64,8%) and bone pain (51,1%). Menstrual disorders in single injectable contraceptives usage was 10.0 folds than CICs. Headache in injectable contraceptives usage was 1.9 folds than in the use of CICs. Menstrual disorders in overweight acceptor 3,8 folds than not overweight.As the ADR observation, the use of CICs is relatively safer than single injectable contraceptive